To solve the equation, we can start by isolating the variable x.
Starting with 11 - 4x = -9, we can subtract 11 from both sides:
11 - 11 - 4x = -9 - 11
This simplifies to:
-4x = -20
Next, we can divide both sides of the equation by -4 to solve for x:
-4x/-4 = -20/-4
This simplifies to:
x = 5
Therefore, the solution to the equation 11 - 4x = -9 is x = 5.
What is the solution of the equation 11−4x=−9 ?(1 point)%0D%0AResponses%0D%0A%0D%0A12%0D%0AStart Fraction 1 over 2 End Fraction%0D%0A%0D%0A−5%0D%0Anegative 5%0D%0A%0D%0A5%0D%0A5%0D%0A%0D%0A−12
1 answer